The Dead Sea scrolls : a full history - Fields, Weston W. (Brill, 2009)
"Since 1998, W.W. Fields has investigated how the Dead Sea Scrolls were discovered, acquired, and edited. This first volume of his "Full History" covers the years 1947-1960. It is rich in detail and discloses the history of the Dead Sea Scrolls based on interviews with the first generation of Dead Sea Scrolls scholars and other people involved in their discovery and publication. In the course of his interviews, Fields has unearthed a wealth of archival material, including diaries and letters previously unknown to the public, which add significant source material to his account. The book is thoroughly illustrated with historic photographs, many in color, illuminating the discovery and editing of the scrolls."--Publisher summary.